ADJUSTING FOR RISK FACTORS FOR READMISSION: IMPLICATIONS FOR MEDICARE'S HOSPITAL READMISSION PROGRAM. (11th November 2018) - Roberts, E T; Zaslavsky, A M; Barnett, M L; Landon, B E; Ding, L; Michael McWilliams, J
Abstract: Medicare's Hospital Readmission Reduction Program (HRRP) penalizes hospitals with high readmission rates, but accounts for few of patients' clinical risk factors—and no social risk factors—for readmission when evaluating hospital performance. Using 2013–14 Medicare claims, we compared the performance of hospitals serving high vs. low proportions of low-income patients and assessed changes in performance assessments after adjusting for clinical and social factors not included in the CMS HRRP risk-adjustment model, including disability, established chronic diseases, poverty, education, and community characteristics. Further adjustments narrowed the average readmission rate difference between hospitals in the highest vs. lowest quintiles of low-income patients by 91.5%, improved the ranking of 10% of hospitals with below-average performance by ≥10.2 percentiles, and moved 8.0% of hospitals out of eligibility for penalties. These results indicate that, by failing to account for salient readmission risk factors, the HRRP penalized some hospitals serving poorer and sicker patients.